2008 International Symposiums on Information Processing 2008
DOI: 10.1109/isip.2008.130
|View full text |Cite
|
Sign up to set email alerts
|

Does Knowledge Sharing Mediate the Relationship between Trust and Firm Performance?

Abstract: Knowledge sharing is crucial for success of companies operating in turbulent and uncertain environments. Knowledge sharing need to be introduced at a rapid pace while at the same time companies have to absorb market information and integrate knowledge during information technology application. Hence, the purpose of this paper is to develop a general model on the critical antecedents and outcome of knowledge sharing. Using structural equations modeling with data collected 208 Chinese firms, the result show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…It thrives among the employees who show mutual respect, openness and trust to one another leading to increased levels of engagement among employees within the organisation. In an empirical examination of the relationships between trust, the presence of the knowledge sharing culture and firm performance, Cheng et al (2008) found that trust positively influences knowledge sharing, while knowledge sharing in turn positively relates to firm performance. Furthermore, Lin and McDonough (2011) found that a knowledge-sharing culture created by strategic leadership can help organisations to improve their innovation ambidexterity.…”
Section: Knowledge Sharing Culturementioning
confidence: 99%
“…It thrives among the employees who show mutual respect, openness and trust to one another leading to increased levels of engagement among employees within the organisation. In an empirical examination of the relationships between trust, the presence of the knowledge sharing culture and firm performance, Cheng et al (2008) found that trust positively influences knowledge sharing, while knowledge sharing in turn positively relates to firm performance. Furthermore, Lin and McDonough (2011) found that a knowledge-sharing culture created by strategic leadership can help organisations to improve their innovation ambidexterity.…”
Section: Knowledge Sharing Culturementioning
confidence: 99%
“…Knowledge sharing in distributed environments requires more a priori trust than face-to-face communication (Riegelsberger, Sasse, & McCarthy, 2003). Investigations have found that a higher level of trust corresponds to greater willingness to share knowledge (Cheng, Hailin, & Hongming, 2008;Quigley, Tesluk, Locke, & Bartol, 2007;Willem & Buelens, 2007). However, trust depends on an implicit set of beliefs, which are vague.…”
Section: Introductionmentioning
confidence: 99%
“…The positive effect of information sharing on trust and the positive relationship between this effect and transformational leadership have been studied widely (Chou, Lin, Chang, &Chuang, 2013;Ryan, 2012). Additionally, the mutual trust and information sharing as the foundation of transformational leadership have been discussed widely in the literature (Casimir, Lee, &Loon, 2012;Cheng, Hailin, &Hongming, 2008;Jain, Sandhu, & Goh, 2015;Sankowska, 2013). The most important characteristics of transformational leaders include self-confidence particularly about future, and to be able to express goals to their followers.…”
Section: Conceptual Frameworkmentioning
confidence: 99%